إعداد كتاب مدرسي لتعليم اللغة العربية كلغة ثانية في الصف الأول الابتدائي في المدارس الإسلامية في فطاني - داؤه، محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
This study designs a textbook suitable for teaching Arabic Language in grade one of elementary Islamic schools in southern Thailand (Pattani). This is preceded by a survey of school teachers evaluating the textbooks currently in use. A questionnaire was distributed to a randomly selected 65 teachers who are involved in the teaching of Arabic Language in various schools. The survey showed that the majority of respondents considered the textbooks currently being used have many shortcomings. The main ones are as follows: 1. The four basic language skills (i.e., listening, speaking, reading and writing) are not sufficiently dealt with. 2. The vocabulary used are not appropriate. 3. The drills and exercises given are not adequately varied. 4. There is neither a teacher,s guide nor a glossary for the books in use. Based on these results, a new textbook is designed. In preparing the book, the abovementioned shortcomings have been rectified. The four basic language skills are specifically emphasised, appropriate vocabulary and language structures are utilised and a variety of drills and exercises are devised and included. It also contains a glossary and a teacher,s guide for the purpose of making teaching systematic and useful.